The comparative value of the horse and mule - Gore, Clyde Jamison (My University, 1907)
Introduction: In the following it will be the object to show the cost of raising, training, and placing on the market, the carriage and coach horse, the draft horse, and the mule. The prices of horses and mules on the markets of the United States for past years shall also be shown and the demands at the present time. One object will be to see which will bring the average stock raiser and farmer the most clear profit, the carriage horse, draft horse, or mule, also which will be the best and most economical to raise under farm conditions. Horses are usually classified into two divisions: Saddle horses and draft horses. They are further classified into the following subdivisions: Saddle horses include, racer, hunter, hack or roadster, and draft horses include carriage and coach horses, and agricultural and heavy draft horses.
Citation: Gore, Clyde Jamison. The comparative value of the horse and mule. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Horses; Mules; Livestock; Livestock Marketing; Theses